BEEF PHYSICAL CHARACTERISTICS OF BALI AND WAGYU CATTLE - Suwiti, Ni Ketut; Susilawati, Ni Nyoman Citra; Swacita, Ida Bagus Ngurah (Buletin Veteriner Udayana, 2017)
A research has been done in order to determine a physical characteristics i.e water holding capacity, acidity level (pH), and cooking loss of beef  from bali and wagyu cattle which were sold in supermarkets around Denpasar. The sampels used in this study were 15 rib eye part of bali and 15 of the wagyu beef  respectively, the sampels from both types were tested on the water holding capacity parameter, the acidity level, and cooking loss. The data were analyzed by qualitative descriptive analysis. The result showed that, the bali beef contained 66.13 % water holding capacity, 5.75 of acidity level  and 31.74 % of coking  loss, whereas the wagyu beef contained 63.84 % water holding capacity, 5.20 of acidity level and 32.29% of cooking loss.